Learning Assistance for Children in Krebet, Sendangsari, Pajangan, and Bantul Villages Through the Learning House Program - Ambar Musoffi; Akhmad Mundzirin Yusuf; Azzarifa Zarni; Devita Anindya Putri; Fina Faradina Drakel; Ikhlasul Amal; Irma Dwi Wahyuni; Nuraini Alfatinah; Rafidah Nur Aini; Retno Sundariningrum; Ricky Setiawan; Rina Triyani; Serin Supriani; Dyahsih Alin Sholihah (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
The results of observations by the Alma Ata University Thematic KKN team showed that in the hamlets of Krebet, Sendangsari, Panjangan, and Bantul there were no guidance or study assistance facilities for children yet. The Thematic KKN team took the initiative to provide tutoring facilities for children through the learning house program. The objectives of implementing learning assistance through learning houses include raising public awareness about the importance of knowledge, producing quality, creative, innovative, and character human resources, and motivating children to be passionate about learning and achieving. The method used begins with the delivery of material, followed by questions and answers on material that has not been understood, then a discussion of the material that has been studied. The results of learning assistance activities show that these activities can help motivate children in learning, increase understanding, foster learning awareness, and increase children's activeness in discussing and asking questions regarding material that is not yet understood.